2013
DOI: 10.1080/01635581.2013.795979
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl Isothiocyanate Inhibits Proliferation and Induces Apoptosis in Pancreatic Cancer CellsIn Vitroand in a MIAPaca2 Xenograft Animal Model

Abstract: Pancreatic cancer is often diagnosed at an advanced stage and it has a poor prognosis which points to an increased need to develop effective chemoprevention strategies for this disease. We examined the ability of phenethyl isothiocyanate (PEITC), a naturally-occurring isothiocyanate found in cruciferous vegetables, to inhibit the growth of pancreatic cancer cells in vitro and in a MIAPaca2 xenograft animal model. Exposure to PEITC inhibited pancreatic cancer cell growth in a dose-dependent manner, with an IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Kallifatidis et al [ 35 ] showed that sulforaphane in combination with TRAIL may be a promising strategy for targeting treatment-resistant pancreatic tumor-initiating cells. Additionally, benzyl isothiocyanate and phenethyl isothiocyanate have also been shown to inhibit proliferation and induce apoptosis in pancreatic cancer cells in vitro and in vivo [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kallifatidis et al [ 35 ] showed that sulforaphane in combination with TRAIL may be a promising strategy for targeting treatment-resistant pancreatic tumor-initiating cells. Additionally, benzyl isothiocyanate and phenethyl isothiocyanate have also been shown to inhibit proliferation and induce apoptosis in pancreatic cancer cells in vitro and in vivo [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of these glucosinolates by the plant enzyme myrosinase generates biologically active isothiocyanates (ITC) 167 and indoles 168 . Many studies have shown that ITCs exert anti-cancer effects through inhibition of HDAC activity and histone hyperacetylation, as reported for sulforaphane (SFN) 169, 170 , allyl isothiocyanate (allyl-ITC) 95 , benzyl isothiocyanate (BITC) 96 , phenylhexyl isothiocyanate (PHITC) 98 , phenethyl isothiocyanate (PEITC) 102 , and other longer-chain isothiocyanates 171 .…”
Section: 0 Protein Acetylation and Dietary Chemopreventive Agentsmentioning
confidence: 99%
“…In these processes, signalling pathways such as AKT, STAT3, histone deacetylase (HDAC) and NF-κB are involved [75]. Xenotransplanted mice treated with phenethyl isothiocyanate show less tumour volume in comparison to controls [89]. Benzyl isothiocynate entails weight loss, physical inactivity, but no toxicity in a mouse model [42,90].…”
Section: Isothiocyanatesmentioning
confidence: 99%